Mutual Cooperation (Gotong Royong) in the View of Islam - Arif Muzayin Shofwan; Devi Candra Nindiya; Heni Krisnawati; Marwan Hayeemaming (International Journal of Islamic Studies Issues, 2025)
Purpose – This study aims to discuss mutual cooperation in Islam as explored from the main sources of the Quran and Hadith. Design/Methodology/Approach – This qualitative descriptive study with literature review uses content analysis to sort data according to the focus of the study. Findings – This study found that Islam encourages mutual cooperation in goodness and piety, and prohibits mutual assistance in significant crimes, as stated in Surah Al-Maidah verse 2 and Surah Ali Imran verse 104.  Mutual cooperation is encouraged because of social awareness among individuals, prioritizing togetherness to create harmony among members of society, as stated in Surah Al-Mujadilah verse 11. Mutual cooperation is also significant in HR. Muslim, HR. Bukhari and Muslim. Islam also allows cooperation and mutual assistance with those of different religions, as stated in Surah At-Taubah verse 6. There are three historical events in Arab civilization related to the culture of mutual cooperation, both before and after the arrival of Islam, namely: the renovation of the Kaaba, the construction of the Prophet's Mosque upon first arriving in Medina, and mutual cooperation in building a trench as a defense during the Battle of Khandaq. Originality/Value – The original value in this study is the discovery of the significance of mutual cooperation with Islamic values based on the Quran and Hadith, which has not been discussed by previous researchers.